KARAKTERISTIK ANOMALI GAYA BERAT DAN NILAI TAHANAN JENIS AUDIO MAGNETOTELURIK (AMT) DI DAERAH PANAS BUMI GIMPU,KABUPATEN SIGI, SULAWESI TENGAH: CHARACTERISTICS OF GRAVITY ANOMALIES AND RESISTIVITY VALUE OF AUDIO MAGNETOTELLURIC (AMT) IN GIMPU GEOTHERMAL AREA, SIGI REGENCY, CENTRAL SULAWESI - Asep Sugianto; Mochamad Nur Hadi (Buletin Sumber Daya Geologi, 2023)
The Gimpu geothermal area is one of the geothermal areas in Central Sulawesi. Surface geothermal manifestations are characterized by the emergence of hot springs with a temperature of 53–67 oC.Geophysics research in this area was conducted to determine the subsurface structure that describes the geothermal system in the Gimpu area. This paper discusses the characteristics of gravity anomalies and resistivity values in magnetotelluric audio (AMT) data. The results show that the distribution pattern of gravity anomalies forms a nearly north-south and northwest-southeast trending lineament. This alignment can also be seen from the results of the First Horizontal Derivative (FHD) analysis. This alignment is thought to be related to the fault structure, which controls the appearance of hot springs on the surface. The results of the 3D gravity modeling show that there is a high-density body around the Langkapa hot springs, presumably as a response from igneous rocks indicating a heat source beneath the surface. The results of 2D AMT modeling show the distribution of low resistivity values of 40 Ohm.m around the Langkapa and Karani hot springs. The distribution pattern of low resistivity values in this area is not like that in volcanic environments in general but is more like the distribution pattern of resistivity in non-volcanic geothermal areas. Therefore, the area that is estimated to be associated with the cap rock in the Gimpu geothermal system has a resistivity value of 40 Ohm.m. The low resistivity zone is located around the Langkapa and Karani hot springs, with an area of about 3 km2.